التأصيل القانوني لإجراءات قضاء الأحداث: دراسة مقارنة - احمد تميم طاهر; فيصل نبيل سعدون (Journal of Legal Sciences, 2019)
Procedural rules followed in the juvenile justice characterized the specificity of it apart from other procedural rules adopted by the ordinary courts and lies that privacy in the importance of the category to which they apply those rules namely,(events) and in need of special procedural treatment category. These measures derives its strength in the legal basis which may be (international) is the general international instruments and which holds the rights to organize rights in general, including the right of juveniles or the so_called rights of the child, or may be aprivate international instrument to children rights that may be of mandatory nature and other inmoral . on the other hand it may be the legal basis (national) constitutional texets, or the public ordinary legislation, or private and it will divide our research into two sections: the first section deals with the foundation (international)for the actions of juvenile justice and the second section deals with the national foundation for those measure taking into account the comparison with some models of the legislation then we conclude our search of the most important result that have been reached.